The first steps in facing your fears: The acceptability of virtual reality and in vivo exposure treatment for specific fears. (April 2023) - Scheveneels, Sara; De Witte, Nele; Van Daele, Tom
Abstract: Phobic individuals are often reluctant to engage in exposure in vivo (IVE). We examined whether providing exposure in virtual reality (VRE) can increase the acceptability. In Study 1, we provided 186 fearful participants with (hypothetical) VRE and IVE treatment offers and examined their willingness to engage in treatment, estimated success, negative beliefs, acceptance/refusal and their preference. Almost 70 % preferred VRE over IVE and acceptance rates were higher for the VRE offer (58 %) than for IVE (35 %). Although participants held fewer negative beliefs about VRE, they did rate IVE as slightly more successful. In Study 2, we examined whether VRE can serve as a stepping stone to IVE in a sample of 102 spider fearful individuals. Willingness to engage, estimated success and negative beliefs about IVE were assessed before and after VRE. After VRE, participants rated IVE as more successful, but were not more willing to engage in IVE, nor were they more inclined to accept an IVE offer. No decreases in negative beliefs were observed. In conclusion, VRE is deemed more acceptable than IVE and could lower refusal rates, hereby resulting in more phobic individuals receiving treatment. Future research should shed light on underlying motivations and associations. Highlights: The acceptability of virtual reality (VRE) and in vivo (IVE) exposure was examined. Fearful participants received a hypothetical treatment offer in VR and IV (Study 1). VRE was deemed more acceptable and associated with less negative beliefs than IVE. The acceptability of IVE was rated before and after a VRE intervention (Study 2). Results do not indicate that VRE increases the acceptability of IVE.